(untitled) (Al-Academy, 2016)
The poster is one of the means which can be communicate with others through it, to transfer ideas that the designer want to focus on, for its importance to accomplish the poster. It’s a visual mean contact aim to submit an idea to the audience to get a clear idea, and that would be through the shapes and subject to submit the idea. Depend on that our goal in this study is to find out, what follows:1-Finding the relationship between the shape and the idea.And the study comes up with several results, like:1-The drawings that contain themes connected with what the designer want to achieve, through the clearness of idea and to make those elements clear by putting more elements to surround the main shape.2-To assure that the strong connection between the shape and theme through expressing the idea of the art work, and to use expressive shapes well known for the audiences.3-The relationship between the shape and theme appears the assurance of the effect of using colors as style and the digital techniques were been used. That will came from the effects of colors on representing the while idea, as vision, as example; the red color and its connections with human life and his culture and educational backgrounds.4-The art techniques have its own features some of them represent symbolic themes and others represent art shape, all those elements to give the designer the ability to express ideas and to reach them. And the symbolism of colors expresses the cultural visions of the viewer to achieve the art sense through the drawings and other shapes or colors